(untitled) (International Seven Journal of Multidisciplinary, 2023)
This article will look at the formation of the teacher’s identity from the perspective of professionalism, based on discussions of teaching practice and entrepreneurial education. It will also seek to identify what the Common National Curriculum Base (BNCC) says about entrepreneurial education. This is a qualitative, bibliographical study. The results of the work allow us to infer that the Ministry of Education has approved the inclusion of Entrepreneurial Education in Schools, describing in the BNCC document the aspects to be worked on with students in the classroom, through the applicability of the Life project. However, it is up to teachers to create means and alternatives for developing and expanding students’ skills and competences. It is also crucial to point out that this work presents aspects of SEBRAE’s Entrepreneurial Education as an educational alternative capable of forming critical, active citizens and that favors the formation of a democratic, fair society that takes into account the appreciation of the human being from a perspective of strengthening collective growth based on sustainability and a better quality of life for all.